2005
DOI: 10.1111/j.1532-5415.2005.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Alcohol and Prescription Drug Interactions in Older People

Abstract: Many older people use alcohol in combination with AI prescription drugs. Clinicians should warn every patient who is prescribed an AI drug about alcohol-drug interactions, especially those at high risk for concomitant exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
6
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 14 publications
(40 reference statements)
6
101
6
3
Order By: Relevance
“…23 The interaction of alcohol and medication puts the elder adult at unnecessary risk of an adverse event and/or non-control of the condition being treated. 9,10,47,48 Within the context of chronic illness management, at-risk alcohol consumption may be responsible for poor medication adherence, intractable hypertension, increased bleeding, and/or poor self-management skills. [35][36][37]49,50 Currently, universal alcohol screening is recommended by the United States Preventive Services Task Force, 51 and recently, the Centers for Medicare and Medicaid Services approved Medicare payment for alcohol screening and four brief counseling sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 The interaction of alcohol and medication puts the elder adult at unnecessary risk of an adverse event and/or non-control of the condition being treated. 9,10,47,48 Within the context of chronic illness management, at-risk alcohol consumption may be responsible for poor medication adherence, intractable hypertension, increased bleeding, and/or poor self-management skills. [35][36][37]49,50 Currently, universal alcohol screening is recommended by the United States Preventive Services Task Force, 51 and recently, the Centers for Medicare and Medicaid Services approved Medicare payment for alcohol screening and four brief counseling sessions.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Moreover, any alcohol use in older adults with specific chronic conditions and/or specific prescription regimes could contribute to adverse medical events. [8][9][10][11] The National Institute on Alcohol Abuse and Alcoholism (NIAAA) defines at-risk drinking for persons over 65 years of age as more than seven drinks per week or more than three drinks on any single day. 8,9 Recent studies have estimated the percentage of older adults that drink in excess of this guideline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated the prevalence of alcohol/medication interactions in older adults. Using data from 83 321 participants aged 65 to 106 years in the Pennsylvania PAcE program (a state-funded program providing prescription benefits to older persons with low to moderate incomes), the researchers found that 19% of those consuming alcohol (20.3% of the sample) took medications that could have negative interactions with alcohol [65].…”
Section: Interaction With Medicationsmentioning
confidence: 99%
“…Alcohol interacts with many other drugs, including prescription, over-the-counter medications and herbal preparations (Izzo & Ernst 2001;Koski et al 2005;Pringle et al 2005;Weathermon & Crabb 1999). The effects of combining alcohol and medication depend on the type, route and dosage of medication, the volume of alcohol consumed, and also on personal factors, such as genetics, gender and comorbid health conditions (Weathermon & Crabb 1999).…”
Section: Appendixesmentioning
confidence: 99%